Indonesian Military Court Law Absolute Competence through Equality before the Law Principle - Ginting, Jamin; Christian, Axel Victor (International Journal of Criminology and Sociology, 2021)
Law Number 31 Year 1997 regulates the jurisdiction of the Indonesian Military Court to handle military members who commit a general crime and military crime based on the Indonesian Penal Code and Indonesian Military Code respectively. However, the General Court also retains jurisdiction over the military members who commit a general crime based on the Indonesian Penal Code. In comparison, Indonesian Civilians who commit a general crime based on the Indonesian Penal Code are only under the General Court. This condition is against the principle of equality before the law as stated in Article 28D.1 of the 1945 Constitution. Indonesia as a state of law must hold this principle. Authors use normative legal research to solve the law issues by reviewing the related laws and the law principles in Indonesia.